Dokumentation in der Hämophilietherapie mit Unterstützung des Deutschen Hämophilieregisters - Haschberger, B.; Hesse, J.; Heiden, M.; Seitz, R.; Schramm, W. (Hämostaseologie, 2010)
The DHR (Deutsches Hämophilieregister, German Haemophilia Register) records patient data on haemophilia A, haemophilia B, von Willebrand disease, and other coagulation factor deficiency disorders. The DHR has been online since 2009. The participation in the DHR leads to additional administrative workload for the hospitals and physicians, but provides many advantages as well: A standard of documentation will be developed to give evidence for the hospitals. They may use their own data as well as with new possibilities for data processing at any time. Reports in accordance with Section 21 TFG (Transfusionsgesetz, German Transfusion Act) are compiled automatically and transmitted to the Paul-Ehrlich-Institut. The DHR may support the searching for patients fulfilling the requirements for participation in a study.
Keywords: Haemophilia; registry; documentation